East meets West: Shadow coaching to support online reflective practice - Byszewski, Anna (Perspect Med Educ, 2018)
OBJECTIVES: A structured, reflection-based electronic portfolio program (ePortfolio), with novel faculty development initiative, involving ‘shadow coaches’, was shared with the newly formed Ottawa-Shanghai Joint School of Medicine (OSJSM). OSJSM is a partnership between Shanghai Jiao Tong University and the University of Ottawa. As the world’s first Sino-Canadian Joint Medical School, OSJSM introduced North American undergraduate medical curriculum to China. ‘Shadow coaching’ involved trans-Pacific pairing of coaches, supplemented by local faculty development. FRAMEWORK: (a) Pre-implementation: The well-established online ePortfolio platform at the University of Ottawa was mirrored at OSJSM. University of Ottawa ePortfolio coaches were recruited to serve as shadow coaches to their OSJSM counterparts. Shadow coaches provided mentoring and resources while maintaining awareness of cross-cultural issues. Faculty development consisted of face-to-face faculty development in Shanghai, several online synchronous sessions, and familiarization of University of Ottawa coaches with the Chinese medical education system. (b) Description/Components: This intervention, introduced in 2016–2017, involved five University of Ottawa shadow coaches paired with five OSJSM ePortfolio coaches. Student reflection encourages open frank discussion which is a new paradigm for Chinese students and faculty. Shadow coaches were encouraged to challenge new OSJSM coaches to widely explore physician roles and competencies. RESULTS: Initial results indicate that the experience served to effectively develop OSJSM coaches’ skills as evidenced by shadow coaches’ review of anonymized OSJSM student reflective writing. CONCLUSIONS: Our project describes a novel tool using shadow coaching for faculty development for a cross-cultural partnership. Similar approaches can be utilized for culturally-sensitive long-distance faculty development.